South Tangerang City's Strategy In Building A Brand Image Through Pamulang Square As Creative Tourism - Yuningsih*, Siska; Sumarni, Lilik; Purwanto, Hari Eko; Jaya, Herdi Wisman (Universitas Syiah Kuala, 2024)
The City of South Tangerang is trying to build a brand image by 2023. The concept of building a South Tangerang square is a positive thing in the environment, especially for the people of South Tangerang City. One of the goals is to provide entertainment with facilities and comfort for the community, such as exercising, gathering with family, especially for South Tangerang residents. South Tangerang Square can also help build and create a positive brand image in society. This research aims to find out the strategies carried out by the South Tangerang City government department in an effort to build a brand image through Pamulang Square as creative tourism. This research was conducted in South Tangerang City in 2023. This research approach is descriptive qualitative. Data were collected through observations at the location of Pamulang Square and interviews with administrators at the South Tangerang City Environmental Service. Source triangulation was carried out by interviewing residents who had visited the square. The results of this research show that the strategy used by the City of South Tangerang can make the public aware of the South Tangerang City square as an environmentally friendly location, thereby making it a location that can be used as a creative public space. The existence of regional, national and even international scale events held in the square shows that the city of South Tangerang is a creative tourist destination, thus attracting more and more tourists or visitors